Bussin : A Bus Tracker Apps using Mobile Application Development Lifecycle Model - Mokhsin @ Misron, Mudiana; Mohd Jais, Anis Nabihah; Inche Zulkifli, Muhammad Danial Aqeem; Ibrahim, Siti Nur Radhiah; Ruzauddin, Nurul Fatihah; Nafrizan, Amy Nazeera (Multidisciplinary Applied Research and Innovation, 2022)
Problem arise on students who takes bus for their daily occasion. The issues appear to be increasing in college. One of the problems found is, new students or first-timers are anxious about boarding a bus without knowing its timetable or destination. Second, students have difficulty tracking arriving buses because they do not always arrive on time. To assist students in overcoming these issues, the idea is to create an app called Bussin to assist students in making their golden time much more valuable. Functions added to the app that allows users to find out which bus they need to catch by searching the designated place. It will provide them a list of buses to choose from and the route they should take. Furthermore, the applications will display all buses travelling through their campus, as well as the projected time for the buses to arrive at the bus stop, they are at. As all the students will be using this apps, we track them soon as they enter the bus that will let users know whether the buses are on their full capacity or not. Hence, from the issues stated, methodology uses for the products are divided of three aspects which is identifying, designing and prototyping phase. The key to the product is to identify the problems faced by certain party and come up with the idea for the solution by designing how the system would be. At last, the prototyping of the product is made to have a clear objective of how the product will be for the final touch.